Potensi Dan Eksistensi Kelembagaan Zakat, Infak, Dan Sedekah: (Studi Eksploratif pada BAZNAS Kabupaten Jombang) - Sokhi Huda; M. Chamim Supaat; Dimyati; M. Syai'in (Sekolah Tinggi Agama Islam At-Tahdzib, Ngoro, Jombang, Indonesia, 2019)
This study aims to explore the potential of zakat, infak, and alms (ZIA) and describe the institutional existence of the National Zakat Management Agency (popularly called BAZNAS) of Jombang Regency. To achieve this goal, the study used a qualitative field approach, expose facto, explorative, and descriptive analysis techniques Miles and Huberman. There are three points of conclusion. First, the potential of ZIA funds in Jombang is Rp. 561.943.512,- per month or Rp. 6,743,322,145,- per year. This amount comes from two agencies, namely the Regional Personnel Agency and the Ministry of Religious Jombang Regency. Potential ZIA funds can be explored further from 26 agencies and other companies in Jombang. Second, the existence of BAZNAS Jombang gets national juridical support in the form of legislation about zakat but not yet armed with Local Regulation of Zakat. Its role recently has been limited to internal coordination meetings, external consultations, unit for collecting zakat (UCZ) training, socialization of Zakat Law, and the collection of infak from Muslim government employees at the Government Office of Jombang Regency. Third, the supporting factors: (1) the normative basis of the Qur'an and the Hadith of the Prophet; (2) juridical foundation in the form of Zakat Law; (3) structural support; (4) operational fund guarantee; (5) organizational management system supported by the availability of building, space, and representative work facilities, and its human resources; (6) cooperation network with agencies and companies in accordance with the needs of ZIS fund raising program. Inhibiting factors: (1) there is no Zakat Regulation or other juridical provision for the collection of ZIS in Jombang Regency; (2) not yet available part of human resources needed according to requirement of distribution development; (3) there is no development of information media available to facilitate the communication of ZIS fund raising program; (4) not yet optimal management function and organizational management as the main strength of ZIS distribution programs. This research recommends the development of further research to be more intensive and optimal about the potential of ZIS fund, especially in BAZNAS of Jombang Regency and generally the Zakat Management Institutions (popularly called LAZ) in Jombang Regency.